Development of Web-Based Komsa Media to Facilitate Logical Thinking and Reading Habits At Elementary School Level - Ardini, Kasimira Prima; Widayat, Edy; Huda, Nuril (Jurnal Teknologi Pendidikan : Jurnal Penelitian dan Pengembangan Pembelajaran, 2024)
Science lessons often involve conceptual material that requires visualization to facilitate students’ understanding. In the fifth grade science learning process, it was found that students had difficulty understanding the subject, lacked enthusiasm for reading,  and the learning media used were monotonous and uninteresting. Consequently, this affected students’ logical thinking abilities. The purpose of this research is to determine the feasibility and effectiveness of the Science Comic (KOMSA) media as a tool to facilitate the logical thinking abilities and reading habits of fifth-grade students in elementary school, specifically on the topic of the water cycle. This study is a developmental research using the 4D approach (define, design, develop, disseminate) with a one-group pretest-posttest design technique conducted at Pangudiluhur Ambarawa Elementary School. The discussion results obtained an average percentage of 87%. The trial results indicated that the learning media falls into the category of high effectiveness with a percentage of 77.18%. Therefore, the Science Comic (KOMSA) as a learning media is deemed suitable and effective for facilitating logical thinking abilities and reading habits.